Active energy ray-curable composition and cured product thereof
By increasing the ratio of monofunctional acrylate and inorganic nanoparticles to the (meth)acrylate compound, and adding multifunctional acrylate and phosphate dispersant, the problem of poor mold release after curing is solved, and high refractive is achieved Compositions of ratio and low viscosity are suitable for the manufacture of optical sheets.
Patent Information
- Application Number
- CN202380039303.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-14
- Filing Date
- 2023-06-23
- Publication Date
- 2024-12-20
AI Technical Summary
The existing multifunctional acrylate resin has fewer polymer structure branches after curing, resulting in poor mold release, easy to remain in the mold, and difficult to achieve both high refractive index and low viscosity.
By setting the monofunctional acrylate content to more than 70% in the (meth)acrylate compound and mixing it with a certain proportion of inorganic nanoparticles, combining multifunctional acrylate and phosphate dispersant, the photopolymerization initiator is optimized. The use of a silane coupling agent forms an active energy ray curable composition with a high refractive index and a low viscosity.
Good mold release and high refractive index are achieved, the residue of cured substances in the mold is reduced, and the properties of low viscosity and high refractive index are combined.
Smart Images

Figure BDA0005125054620000121 
Figure BDA0005125054620000211 
Figure BDA0005125054620000251
Abstract
Description
Technical Field
[0001] The present invention relates to an active energy ray-curable composition and a cured product thereof.
[0002] This application claims priority based on Japanese Patent Application No. 2022-106541 filed in Japan on June 30, 2022, and Japanese Patent Application No. 2022-146130 filed in Japan on September 14, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] In recent years, optical sheets with functions such as improving brightness and expanding viewing angles are used in displays such as liquid crystal display devices. Such optical sheets usually have a substrate and an optical functional layer having a fine concave-convex structure on the substrate, and light is converted by geometric optical effects such as refraction in the concave-convex shape, thereby reflecting the desired function. Such a concave-convex shape is mainly manufactured by a method of shaping a resin material using a mold, so the material used for the optical functional layer is required to be solvent-free and low-viscosity, and further, it is required that the optical functional layer is not damaged when it is peeled off (demolded) from the mold after curing.
[0004] On the other hand, with the thinning of displays and the reduction of power consumption, the materials used in the optical functional layer are required to have a high refractive index. In order to cope with the above situation, a method of using a monofunctional (meth)acrylate with a high refractive index and low viscosity, or adding organic or inorganic high refractive index particles has been proposed (for example, Patent Documents 1 to 3).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2020 / 250721
[0008] Patent Document 2: Japanese Patent Application Publication No. 2013-249439
[0009] Patent Document 3: Japanese Patent Application Publication No. 2010-85539 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] However, for resins with a low content of multifunctional (meth)acrylate, the polymer structure after curing has fewer branches, so there is a problem that damage is easily generated during demolding and the resin remains in the mold. Therefore, a material with good demolding properties, high refractive index and low viscosity is required.
[0012] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an active energy ray-curable composition having good releasability, a high refractive index, and a low viscosity, and a cured product thereof.
[0013] Solutions for solving problems
[0014] The present invention achieves a high refractive index and exhibits good mold release properties by setting the content of monofunctional (meth)acrylate in the (meth)acrylate compound to a specific range and mixing a certain amount of inorganic nanoparticles or more, and thus a patent application has been completed.
[0015] The present disclosure includes the following embodiments.
[0016] [1] An active energy ray-curable composition comprising inorganic nanoparticles (A), a (meth)acrylate compound (B) and a photopolymerization initiator (C),
[0017] The (meth)acrylate compound (B) comprises a monofunctional (meth)acrylate (B1),
[0018] The content of the monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B) is 70% by mass or more,
[0019] The mass mixing ratio [(A) / (B1)] of the inorganic nanoparticles (A) to the monofunctional (meth)acrylate (B1) is in the range of 0.5 to 3.
[0020] [2] The active energy ray-curable composition according to [1], wherein the content of the inorganic nanoparticles (A) in the active energy ray-curable composition is 30% by mass or more.
[0021] [3] The active energy ray-curable composition according to [1] or [2], wherein the inorganic nanoparticles (A) are one or more selected from the group consisting of zirconium oxide, silicon dioxide, barium sulfate, zinc oxide, barium titanate, cerium oxide, aluminum oxide, and titanium oxide.
[0022] [4] The active energy ray-curable composition according to any one of [1] to [3], wherein the (meth)acrylate compound (B) further comprises a polyfunctional (meth)acrylate (B2),
[0023] The content of the monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B) is in the range of 70 to 90% by mass.
[0024] The content of the polyfunctional (meth)acrylate (B2) in the (meth)acrylate compound (B) is in the range of 10 to 30% by mass.
[0025] [5] The active energy ray-curable composition according to any one of [1] to [4], wherein the monofunctional (meth)acrylate (B1) contains a compound having two aromatic rings in one molecule.
[0026] [6] The active energy ray-curable composition according to [5], wherein the content of the compound containing two aromatic rings in one molecule in the monofunctional (meth)acrylate (B1) is 50% by mass or more.
[0027] [7] The active energy ray-curable composition according to any one of [1] to [6], further comprising a dispersant (D),
[0028] The above-mentioned dispersant (D) contains a phosphoric acid ester compound,
[0029] The above-mentioned phosphate ester compound has at least one (meth)acryloyl group and at least one polyester chain.
[0030] [8] The active energy ray-curable composition according to any one of [1] to [7], which has a viscosity at 25° C. of 1200 mPa·s or less.
[0031] [9] A cured product of the active energy ray-curable composition according to any one of [1] to [8].
[0032]
[10] The cured product according to [9], which has a refractive index (589 nm) at 25°C of 1.65 or more.
[0033]
[11] An optical sheet comprising the cured product described in [9].
[0034] Effects of the Invention
[0035] According to the present invention, there can be provided an active energy ray-curable composition having good releasability, a high refractive index and a low viscosity, and a cured product thereof. DETAILED DESCRIPTION
[0036] The present invention will be described in more detail below. It should be noted that the present invention is not limited to the embodiments described below.
[0037] “~” means a value greater than or equal to the value before “~” and less than or equal to the value after “~”. “(Meth)acrylic acid” is a general term for acrylic acid and methacrylic acid, and “(meth)acrylate compound (B)” is a general term for acrylate compounds and methacrylate compounds.
[0038] (Active energy ray-curable composition)
[0039] The active energy ray-curable composition of the present embodiment contains inorganic nanoparticles (A), a (meth)acrylate compound (B) and a photopolymerization initiator (C). The (meth)acrylate compound (B) contains 70 parts by mass or more of a monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B). In addition, the mass mixing ratio [(A) / (B1)] of the inorganic nanoparticles (A) to the monofunctional (meth)acrylate (B1) is in the range of 0.5 to 3.
[0040] [Inorganic nanoparticles (A)]
[0041] The inorganic nanoparticles (A) of the present embodiment are preferably at least one selected from the group consisting of zirconium oxide, silicon dioxide, barium sulfate, zinc oxide, barium titanate, cerium oxide, aluminum oxide, and titanium oxide.
[0042] The crystal structure of the inorganic nanoparticles (A) of the present embodiment is not particularly limited either. For example, in the case of zirconium oxide, a monoclinic system is preferred because a cured product having excellent dispersion stability, high light transmittance and high refractive index can be obtained.
[0043] The inorganic nanoparticles (A) of the present embodiment can use generally known ones, and the shape of the particles is not particularly limited, and can also be, for example, spherical, hollow, porous, rod-shaped, plate-shaped, fibrous, or any of amorphous. Among them, from the viewpoint of obtaining a cured product with excellent dispersion stability, high transmittance and high refractive index, spherical is preferred.
[0044] <Zirconium oxide nanoparticles>
[0045] The inorganic nanoparticles (A) of this embodiment are more preferably zirconium oxide nanoparticles. The zirconium oxide nanoparticles may be generally known ones, and the shape of the particles is not particularly limited, and examples thereof include spherical, hollow, porous, rod-shaped, and fibrous shapes, among which spherical shapes are preferred.
[0046] The average primary particle size of the zirconium oxide nanoparticles of the present embodiment is preferably 1 to 50 nm, more preferably 1 to 30 nm. The crystal structure is not particularly limited, but is preferably a monoclinic system.
[0047] It should be noted that the average primary particle size in the present invention can be measured using a method for directly measuring the size of primary particles by electron microscope photographs using TEM (transmission electron microscope). As a measuring method, for example, the minor axis diameter and major axis diameter of the primary particles of each inorganic fine particle can be enumerated, and the average is set as the method for the average primary particle size of the primary particles.
[0048] Specific examples of the zirconium oxide nanoparticles of the present embodiment include UEP-100 manufactured by Dai-ichi Kizenso Kagaku Kogyo Co., Ltd. (average primary particle size: 11 nm) and PCS manufactured by Nippon Denko K.K. (average primary particle size: 20 nm).
[0049] In addition, the mass mixing ratio of the inorganic nanoparticles (A) to the monofunctional (meth)acrylate (B1) [(A) / (B1)] is in the range of 0.5 to 3, preferably in the range of 0.7 to 2.5, more preferably in the range of 0.85 to 2, and even more preferably in the range of 1 to 1.5. By setting it in this range, good mold release properties and low viscosity can be achieved.
[0050] [(Meth)acrylate compound (B)]
[0051] As the (meth)acrylate compound (B) of the present embodiment, as long as the monofunctional (meth)acrylate (B1) containing 70 parts by mass or more in the above-mentioned (meth)acrylate compound (B), there is no particular limitation, and examples include monofunctional (meth)acrylate (B1) or multifunctional (meth)acrylate (B2) having (meth)acryloyl group, (meth)acryloyloxy group for forming optical sheets known in the past. Oligomers or prepolymers can be used as needed. The (meth)acrylate compound (B) of the present embodiment preferably includes a monofunctional (meth)acrylate (B1) having one active energy ray curable group (hereinafter sometimes referred to as "(B1) component") and a multifunctional (meth)acrylate (B2) having two or more active energy ray curable groups (hereinafter sometimes referred to as "(B2) component"). The above-mentioned active energy ray curable group is preferably a (meth)acryloyl group.
[0052] In addition, the (meth)acrylate compound (B) of this embodiment is set not to contain the dispersant (D) which has a (meth)acryloyl group, and the silane coupling agent (E) which has a (meth)acryloyl group or a (meth)acryloyloxy group.
[0053] These components (B1) and (B2) are described in detail below.
[0054] <Monofunctional (meth)acrylate (B1)>
[0055] The above-mentioned monofunctional (meth)acrylate (B1) is a monofunctional (meth)acrylate having one active energy ray-curable group, and may be a chain aliphatic or cyclic alicyclic or aromatic (meth)acrylate containing heteroatoms such as halogen atoms, sulfur atoms, oxygen atoms or nitrogen atoms. For example, the monofunctional (meth)acrylate described in the above-mentioned Patent Document 1 can be used.
[0056] Examples of the monofunctional (meth)acrylate (B1) include aromatic mono(meth)acrylate compounds, aliphatic mono(meth)acrylate compounds, alicyclic mono(meth)acrylate compounds, heterocyclic mono(meth)acrylate compounds, and hydroxyl-containing mono(meth)acrylate compounds.
[0057] In addition, examples of the monofunctional (meth)acrylate (B1) include: polyoxyalkylene-modified mono(meth)acrylate compounds in which a polyoxyalkylene chain such as a polyoxyethylene chain, a polyoxypropylene chain, or a polyoxytetramethylene chain is introduced into the molecular structure of the various mono(meth)acrylate compounds described above; lactone-modified mono(meth)acrylate compounds in which a (poly)lactone-derived structure is introduced into the molecular structure of the various mono(meth)acrylate compounds described above; and the like.
[0058] Examples of the aromatic mono(meth)acrylate compound include benzyl(meth)acrylate, phenyl(meth)acrylate, phenoxy(meth)acrylate, phenoxyethyl(meth)acrylate, phenoxyethoxyethyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, phenoxybenzyl(meth)acrylate, biphenylmethyl(meth)acrylate, benzylbenzyl(meth)acrylate, phenylphenoxyethyl(meth)acrylate, phenylphenol(EO)n(meth)acrylate, and phenol(EO)n(meth)acrylate.
[0059] Examples of the aliphatic mono(meth)acrylate compound include methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, tert-butyl(meth)acrylate, n-pentyl(meth)acrylate, n-hexyl(meth)acrylate, n-octyl(meth)acrylate, isooctyl(meth)acrylate, and 2-ethylhexyl(meth)acrylate.
[0060] Examples of the alicyclic mono(meth)acrylate compound include cyclohexyl(meth)acrylate, isobornyl(meth)acrylate, adamantyl mono(meth)acrylate, cyclohexylmethyl(meth)acrylate, cyclohexylethyl(meth)acrylate, dicyclopentanyl(meth)acrylate, dicyclopentyloxyethyl(meth)acrylate, dicyclopentenyl(meth)acrylate, and dicyclopentenyloxyethyl(meth)acrylate.
[0061] Examples of the heterocyclic mono(meth)acrylate compound include glycidyl(meth)acrylate and tetrahydrofurfuryl acrylate.
[0062] Examples of the hydroxyl group-containing mono(meth)acrylate compound include hydroxyethyl(meth)acrylate, hydroxypropyl(meth)acrylate, and hydroxybutyl(meth)acrylate.
[0063] Examples of the lactone-modified mono(meth)acrylate compound include caprolactone-modified tetrahydrofurfuryl (meth)acrylate.
[0064] The monofunctional (meth)acrylate (B1) preferably contains an aromatic mono(meth)acrylate compound, and more preferably contains a compound containing two aromatic rings in one molecule. The compound containing two aromatic rings in one molecule is particularly preferably biphenyl methyl (meth)acrylate.
[0065] Examples of the compound containing two aromatic rings in one molecule (aromatic mono(meth)acrylate compound) include phenoxybenzyl(meth)acrylate, biphenylmethyl(meth)acrylate, benzylbenzyl(meth)acrylate, phenylphenoxyethyl(meth)acrylate, phenylphenol(EO)n(meth)acrylate, and (1-naphthyl)methyl acrylate.
[0066] As a specific example of the said monofunctional (meth)acrylate (B1), the following monofunctional (meth)acrylate used in Example is mentioned, for example.
[0067] Compound (B1-1): o-phenylphenol (EO) acrylate, trade name: KOMERATE A011 (manufactured by Green Chemical Co., Ltd.)
[0068] Compound (B1-2): biphenyl methyl acrylate, trade name: MIRAMER M1192 (manufactured by MIWON SPECIALTYCHEMICAL CO., LTD.)
[0069] Compound (B1-3): 3-phenoxybenzyl acrylate, trade name: KOMERATE A008 (manufactured by Green Chemical Co., Ltd.)
[0070] Compound (B1-4): (1-naphthyl)methyl acrylate, trade name: LIGHT ACRYLATE NMT-A (manufactured by Kyoei Chemical Co., Ltd.)
[0071] Compound (B1-5): phenoxyethyl acrylate, trade name: Photomer 4035 (manufactured by IGM Resins Inc.)
[0072] Compound (B1-6): benzyl acrylate, trade name: MIRAMER M1182 (manufactured by MIWON SPECIALTY CHEMICAL CO., LTD.)
[0073] The monofunctional (meth)acrylate (B1) may be used alone or in combination of two or more.
[0074] The content of the monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B) is 70% by mass, preferably 75% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more. In addition, it is preferably 95% by mass or less, and more preferably 90% by mass or less. The reason is that when the content of the monofunctional (meth)acrylate (B1) is within the above range, the mold release property is good, the refractive index is high, and the viscosity is low.
[0075] When the monofunctional (meth) acrylate (B1) is included in a compound (aromatic mono (meth) acrylate compound) containing 2 aromatic rings in 1 molecule, the content of the compound containing 2 aromatic rings in 1 molecule of the monofunctional (meth) acrylate (B1) is preferably 50% by mass or more, more preferably 60% by mass or more, and further more preferably 70% by mass or more. As the compound containing 2 aromatic rings in 1 molecule, biphenyl methyl (meth) acrylate can be cited. In addition, the content of the above-mentioned compound is not particularly limited, and the higher the numerical value, the better. Barely speaking, from the viewpoint of demoulding property, it is preferably less than 95% by mass, more preferably less than 90% by mass.
[0076] When the compound containing two aromatic rings in one molecule in the monofunctional (meth)acrylate (B1) is biphenyl methyl acrylate, the compound is excellent in substrate adhesion in addition to the refractive index, viscosity and mold release properties.
[0077] [Multifunctional (meth)acrylate (B2)]
[0078] The (meth)acrylate compound (B) of the present embodiment preferably contains a polyfunctional (meth)acrylate (B2) (sometimes referred to as "(B2) component") in addition to the monofunctional (meth)acrylate (B1) of the present embodiment.
[0079] The polyfunctional (meth)acrylate (B2) is preferably a polyfunctional (meth)acrylate having three or more active energy ray-curable groups. It may be a chain aliphatic, cyclic alicyclic or aromatic (meth)acrylate containing heteroatoms such as halogen atoms, sulfur atoms, oxygen atoms or nitrogen atoms, and for example, the polyfunctional (meth)acrylate described in Patent Document 1 may be used.
[0080] Examples of the polyfunctional (meth)acrylate (B2) include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, tetrabutanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, Glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, dicyclopentyl di(meth)acrylate, glycerol di(meth)acrylate, neopentyl glycol hydroxypivalate di(meth)acrylate, caprolactone-modified hydroxypivalate neopentyl glycol ester di(meth)acrylate, tetrabromobisphenol A di(meth)acrylate, hydroxypivalaldehyde-modified trimethylolpropane di(meth)acrylate, bisphenol fluorene di(meth)acrylate, bisphenol fluorene (EO) n Di(meth)acrylate, bisphenol A (EO) n Di(meth)acrylate, trimethylolpropane (EO) n Polyfunctional (meth)acrylates (B2) such as tri(meth)acrylate, 1,4-cyclohexanedimethanol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol tri(meth)acrylate, alkyl-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tetraacrylate, di-trimethylolpropane tetra(meth)acrylate, epoxy (meth)acrylate, urethane (meth)acrylate and polyester (meth)acrylate.
[0081] The multifunctional (meth)acrylate (B2) may be used alone or in combination of two or more thereof. In addition, from the viewpoint of obtaining a (meth)acrylic resin having excellent drying properties, ink fluidity and high-speed printing suitability, among these, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, di-trimethylolpropane tetra(meth)acrylate, a reaction product of pentaerythritol and acrylic acid, a reaction product of dipentaerythritol and acrylic acid, and the like are preferred.
[0082] As an example of the multifunctional (meth)acrylate (B2) of the present embodiment, a mixture of a multifunctional (meth)acrylate having three active energy ray-curable groups and a multifunctional (meth)acrylate having four active energy ray-curable groups can be cited. As a specific example thereof, a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (containing about 30 to 70% by mass of tri-form and about 70 to 30% by mass of tetra-form) can be cited. As this mixture, for example, "ARONIX M-305" (manufactured by Toagosei Co., Ltd., a reaction product of pentaerythritol and acrylic acid, containing about 60% of tri-form, hydroxyl value 116 mgKOH / g) used in the examples can be cited.
[0083] When the content of the monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B) is in the range of 70 to 90% by mass, the content of the polyfunctional (meth)acrylate (B2) in the (meth)acrylate compound (B) of the present embodiment is preferably in the range of 10 to 30% by mass, more preferably 10 to 25% by mass, and even more preferably 10 to 20% by mass. Within this range, the refractive index is excellent.
[0084] [Photopolymerization initiator (C)]
[0085] The photopolymerization initiator (C) of the present embodiment is not particularly limited as long as it has the function of initiating polymerization of the (meth)acryloyl group of the (meth)acrylate compound (B) of the present embodiment by light excitation, and examples thereof include intramolecular bond cleavage type photopolymerization initiators (C), intramolecular hydrogen abstraction type photopolymerization initiators (C), etc. For example, monocarbonyl compounds, dicarbonyl compounds, acetophenone compounds, benzoin ether compounds, acylphosphine oxide compounds, aminocarbonyl compounds, etc. can be used.
[0086] Examples of the intramolecular bond cleavage type photopolymerization initiator (C) include acetophenone series such as diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, benzyl dimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propane-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone; benzoins such as benzoin, benzoin methyl ether, and benzoin isopropyl ether; acylphosphine oxide series such as 2,4,6-trimethylbenzoin diphenylphosphine oxide; diphenylethanedione, methylphenylglyoxylate, and the like.
[0087] Examples of the intramolecular hydrogen abstraction type photopolymerization initiator (C) include benzophenone, methyl o-benzoylbenzoate-4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, acryloyl benzophenone, 3,3',4,4'-tetrakis(tert-butylperoxycarbonyl)benzophenone, 3,3'-dimethyl-4-methylbenzophenone, Benzophenone series of oxybenzophenone; thioxanthone series such as 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone; aminobenzophenone series such as Michler's ketone and 4,4'-diethylaminobenzophenone; 10-butyl-2-chloroacridone, 2-ethylanthraquinone, 9,10-phenanthrenequinone, camphorquinone, etc.
[0088] The photopolymerization initiator (C) is preferably 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
[0089] Examples of commercially available products of the photopolymerization initiator (C) include Omnirad-184, 651, 500, 907, 127, 369, 784, 2959, and TPO-H manufactured by IGM-Resins Co., Ltd. and Esacure ONE manufactured by DKSH Japan Co., Ltd.
[0090] From the viewpoint of obtaining a cured coating film having excellent curability even when added in a small amount, Omnirad-907 and Omnirad-TPO-H are preferred, and from the viewpoint of less coloration, Omnirad-184 is particularly preferred.
[0091] The photopolymerization initiator (C) is not limited to the above-mentioned compounds, and may be any substance as long as it has the ability to initiate polymerization by ultraviolet rays. The photopolymerization initiator (C) may be used alone or in combination of two or more.
[0092] The amount of the photopolymerization initiator (C) is not particularly limited, but is preferably used in a range of 0.1 to 10 parts by mass, more preferably in a range of 1 to 5 parts by mass, relative to 100 parts by mass of the total non-volatile components of the active energy ray-curable composition of the present embodiment. As a sensitizer, a known organic amine or the like may also be added.
[0093] In addition, in addition to the above-mentioned radical polymerization initiator, an initiator for cationic polymerization may be used in combination.
[0094] Specific examples of the photopolymerization initiator (C) according to the present embodiment include Runtecure 1108 (manufactured by Runtec Chemical Co., Ltd., structural formula or compound name: 2,4,6-trimethylbenzoyldiphenylphosphine oxide).
[0095] The content of the photopolymerization initiator (C) is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, based on the mass of the nonvolatile components in the composition.
[0096] The nonvolatile content of the composition refers to the total weight of all components of the composition excluding the solvent contained in the composition.
[0097] [Dispersant (D)]
[0098] The active energy ray-curable composition of the present embodiment preferably further contains a dispersant (D) (sometimes referred to as “component (D)”), and the dispersant (D) more preferably contains a phosphoric acid ester.
[0099] <Phosphate ester>
[0100] The phosphoric acid ester in the present embodiment is not particularly limited, and examples thereof include phosphoric acid esters having a polyester chain and phosphoric acid esters having a (meth)acryloyl group.
[0101] As a phosphoric acid ester which has a polyester chain, DISPERBYK-110 and DISPERBYK-111 (made by BYK Japan Co., Ltd.) are mentioned, for example.
[0102] In addition, as the phosphate ester with (meth) acryloyl group, the one shown in the following structural formula (1) can be enumerated. In this case, since the obtained inorganic microparticle dispersion has excellent dispersion stability, and the curable composition containing it is low viscosity, a cured coating film with high refractive index performance and excellent anti-bleeding property can be formed, and thus it is preferred.
[0103]
[0104] (R 1 is a hydrogen atom or a methyl group, R 2 is an alkylene chain having 2 to 4 carbon atoms. In addition, x is an integer of 4 to 10, y is an integer greater than 1, and n is an integer of 1 to 3.
[0105] In the phosphate compound represented by the above structural formula (1), x in the formula is preferably 4 or 5, and y is preferably an integer of 2 to 7. The reason for this is that the obtained active energy ray-curable composition has a low viscosity and can form a cured coating film having a high refractive index performance and excellent anti-bleeding properties. In addition, the dispersant (D) represented by the above structural formula (1) may also be a mixture in which n in the formula is 1, 2 and / or 3.
[0106] From the viewpoint of forming a cured coating film having high refractive index performance and excellent bleed resistance, the content of the phosphate compound in the active energy ray-curable composition is more preferably in the range of 5 to 40 parts by mass, and even more preferably in the range of 10 to 25 parts by mass, relative to 100 parts by mass of zirconium oxide.
[0107] [Silane coupling agent (E)]
[0108] The active energy ray-curable composition of the present embodiment may further contain a silane coupling agent (E) (sometimes referred to as "component (E)"). Examples of the silane coupling agent (E) of the present embodiment include (meth)acryloxy-based silane coupling agents such as 3-(meth)acryloxypropyltrimethylsilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, and 3-(meth)acryloxypropyltriethoxysilane;
[0109] Vinyl silane coupling agents such as allyltrichlorosilane, allyltriethoxysilane, allyltrimethoxysilane, diethoxymethylvinylsilane, trichlorovinylsilane, vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(2-methoxyethoxy)silane;
[0110] Epoxy silane coupling agents such as diethoxy (glycidoxypropyl) methyl silane, 2-(3,4-epoxycyclohexyl) ethyl trimethoxy silane, 3-glycidoxypropyl trimethoxy silane, 3-glycidoxypropyl methyl diethoxy silane, and 3-glycidoxypropyl triethoxy silane;
[0111] Styrene-based silane coupling agents such as p-phenylenedimethoxysilane;
[0112] Amino silane coupling agents such as N-2(aminoethyl)3-aminopropylmethyldimethoxysilane, N-2(aminoethyl)3-aminopropyltrimethoxysilane, N-2(aminoethyl)3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, and N-phenyl-3-aminopropyltrimethoxysilane;
[0113] Urea-based silane coupling agents such as 3-ureidopropyltriethoxysilane;
[0114] Chloropropyl-based silane coupling agents such as 3-chloropropyltrimethoxysilane; mercapto-based silane coupling agents such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane;
[0115] Sulfide silane coupling agents such as bis(triethoxysilylpropyl)tetrasulfide;
[0116] Isocyanate silane coupling agents such as 3-isocyanatepropyltriethoxysilane;
[0117] Aluminum-based silane coupling agents such as acetoalkoxy aluminum diisopropylate, etc.
[0118] The silane coupling agent (E) may be used alone or in combination of two or more thereof. Among these, 3-(meth)acryloxypropyltrimethoxysilane is preferred because of its good compatibility with the acrylate compound (B).
[0119] The amount of the silane coupling agent (E) used in this embodiment is preferably in the range of 10 to 30 parts by mass relative to 100 parts by mass of zirconium oxide. The reason for this is that the obtained active energy ray-curable composition has excellent dispersion stability and, due to its low viscosity, can form a cured coating film having high refractive index performance and excellent anti-bleeding properties.
[0120] [Solvent]
[0121] The active energy ray-curable composition of the present embodiment may contain a solvent.
[0122] As solvent, there is no particular restriction, and various known organic solvents can be used. Specifically, for example, cyclohexanone, methyl isobutyl ketone, methyl ethyl ketone, acetone, acetylacetone, toluene, xylene, n-butanol, isobutyl alcohol, tert-butanol, n-propanol, isopropyl alcohol, ethanol, methanol, 3-methoxy-1-butanol, 3-methoxy-2-butanol, ethylene glycol monomethyl ether, ethylene glycol mono-n-butyl ether, 2-ethoxyethanol, 1-methoxy-2-propanol, diacetone alcohol, ethyl lactate, butyl lactate, propylene glycol monomethyl ether, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, 2-ethoxyethyl acetate, butyl acetate, isoamyl acetate, dimethyl adipate, dimethyl succinate, dimethyl glutarate, tetrahydrofuran, methyl pyrrolidone, etc. Among these, methyl ethyl ketone is preferred. These organic solvents can also be used in combination of two or more.
[0123] The active energy ray-curable composition of the present embodiment may contain, for example, a solvent used when synthesizing each resin.
[0124] The active energy ray-curable composition of the present embodiment may be mixed with the (meth)acrylate compound (B) and the photopolymerization initiator (C) after preparing a dispersion of the inorganic nanoparticles (A) by mixing the inorganic nanoparticles (A), a solvent, and optional components.
[0125] The example containing the above-mentioned solvent is an example, and even if the solvent is contained in the process of preparing the active energy ray-curable composition of the present embodiment, it is preferred that the solvent is finally volatilized and the content of the solvent is extremely small. Therefore, when the active energy ray-curable composition of the present embodiment contains a solvent, the content of the solvent in the above-mentioned active energy ray-curable composition is preferably 0 to 5% by mass, and more preferably 0 to 0.1% by mass.
[0126] [Viscosity of Active Energy Ray-Curable Composition]
[0127] The active energy ray-curable composition of this embodiment preferably has a viscosity of 6500 Pa·s or less at 25°C, more preferably 3500 mPa·s or less, and even more preferably 1500 mPa·s or less at 25°C. It is preferably 1000 mPa·s or more. Within this range, the composition has coating suitability.
[0128] [Method for preparing active energy ray-curable composition]
[0129] The method for preparing the active energy ray-curable composition of the present embodiment is not particularly limited. For example, a method of preparing the composition by mixing the dispersion of the inorganic nanoparticles (A), the monofunctional (meth)acrylate (B1), the photoinitiator, and the polyfunctional (meth)acrylate (B2) as required, and various other additives after obtaining a dispersion of the inorganic nanoparticles (A).
[0130] The method for producing the active energy ray-curable composition of the present embodiment preferably includes: a step of preparing an inorganic nanoparticle (A) dispersion; and a step of mixing the inorganic nanoparticle (A) dispersion, the monofunctional (meth)acrylate (B1), a photoinitiator, and a polyfunctional (meth)acrylate (B2) as required and other various additives.
[0131] The mixing method is not particularly limited, and an example thereof includes a method using a media-type wet disperser.
[0132] In the step of preparing the inorganic nanoparticle (A) dispersion, at least a portion of the monofunctional (meth)acrylate (B1) may be added, and at least a portion of the polyfunctional (meth)acrylate (B2) may be added as needed.
[0133] <Inorganic nanoparticle (A) dispersion>
[0134] The inorganic nanoparticle (A) dispersion of the present embodiment preferably comprises, for example, the inorganic nanoparticle (A), the solvent, and the dispersant (D) as the additive. The inorganic nanoparticle (A) dispersion of the present embodiment may further comprise at least a portion of the monofunctional (meth)acrylate (B1), and may also comprise at least a portion of the multifunctional (meth)acrylate (B2) as required.
[0135] The above-mentioned dispersant (D) preferably has an acid value in the range of 50 to 300 mgKOH / g. The above-mentioned dispersant (D) is generally prone to inorganic nano aggregation in the system due to the interaction between the inorganic nanoparticles (A) and other resin components contained in the active energy ray curable composition of this embodiment, and the stability of the active energy ray curable composition is reduced, or the transparency of the cured coating film is reduced. By using a dispersant (D) with an acid value in the range of 50 to 300 mgKOH / g, a curable composition with excellent stability over time can be obtained, which not only has a high refractive index in the cured product, but also has excellent light transmittance and scratch resistance.
[0136] The inorganic nanoparticle (A) dispersion of this embodiment further preferably contains the above-mentioned silane coupling agent (E) as the above-mentioned additive. Functional groups can be introduced onto the surface of the above-mentioned inorganic nanoparticle (A) using the above-mentioned various silane coupling agents (E) and the like.
[0137] The method for producing the inorganic nanoparticle (A) dispersion of the present embodiment is not particularly limited, and examples thereof include a method of producing the dispersion by dispersing a raw material containing the inorganic nanoparticles (A), the dispersant (D), and, if necessary, the silane coupling agent (E) in a medium-type wet disperser.
[0138] The media-type wet disperser used in the above-mentioned production method can be any commonly known one without limitation, and examples thereof include a bead mill (Star Mill LMZ-015 manufactured by Ashizawa Finetech Co., Ltd., Ultra Apex Mill UAM-015 manufactured by Kotobuki Industry Co., Ltd., etc.).
[0139] The medium used in the disperser is not particularly limited as long as it is a commonly known bead, and preferably zirconia, alumina, silica, glass, silicon carbide, and silicon nitride can be mentioned. The average particle size of the medium is preferably 50 to 500 μm, and more preferably 50 to 200 μm. If the particle size is 50 μm or more, the impact force on the raw material powder is appropriate, and the dispersion does not require excessive time. On the other hand, if the particle size of the medium is 500 μm or less, the impact force on the raw material powder is appropriate, so the increase in the surface energy of the dispersed particles can be suppressed, and re-aggregation can be prevented.
[0140] In addition, the dispersion process time can be shortened by using a two-stage method of using a large-particle size medium with a strong impact force in the initial stage of pulverizing the raw material powder, and then using a small-particle size medium that is less likely to cause re-aggregation after the particle size of the dispersed particles becomes smaller.
[0141] Furthermore, from the viewpoint of suppressing a decrease in the light transmittance of the obtained dispersion, it is preferred to use a sufficiently ground medium.
[0142] In the above-mentioned manufacturing method using a media-type wet disperser, the order of adding the raw materials to the disperser is not particularly limited. By at least supplying the above-mentioned dispersant (D) last, a curable composition with excellent dispersion stability can be obtained with the use of a small amount of dispersant (D). More specifically, there can be mentioned a method in which raw materials other than the above-mentioned dispersant (D) are first added, and operations such as mixing or pre-dispersion are performed, and then the dispersant (D) is added last to perform the main dispersion process.
[0143] After the dispersion is completed, various additives may be added according to the application, or volatile components may be removed by distillation, thereby obtaining the curable composition of the present invention.
[0144] In addition, since the inorganic nanoparticles (A) partially aggregate in the dispersion, the particle size (set as the average particle size) of the inorganic nanoparticles (A) in the inorganic nanoparticle (A) dispersion is larger than the average primary particle size of the inorganic nanoparticles (A) serving as the raw material of the inorganic nanoparticle (A) dispersion.
[0145] Therefore, from the viewpoint of obtaining a cured product having a high refractive index and excellent light transmittance, the average particle size of the inorganic nanoparticles (A) in the inorganic nanoparticle (A) dispersion is preferably 100 nm or less, more preferably in the range of 20 to 100 nm.
[0146] [Characteristics of Active Energy Ray-Curable Composition]
[0147] The active energy ray-curable composition of the present embodiment has good releasability, a high refractive index, and a low viscosity. Examples of the active energy ray-curable composition of the present embodiment include LUXYDIR (registered trademark) (manufactured by DIC Corporation).
[0148] (cured material)
[0149] The cured product of this embodiment is a cured product of the active energy ray-curable composition of this embodiment described above and can be used for various purposes such as optical lenses, optical films, antireflection materials, thin film packaging materials, optical adhesives, optical bonding agents, and diffusion microlenses.
[0150] The shape of the cured product of this embodiment is not particularly limited, and may be a flat sheet with a smooth surface, a sheet with a fine concavoconvex structure, a sheet with a curved surface like a concave lens or a convex lens, or the like, depending on the application.
[0151] The refractive index (589nm) of the cured product of this embodiment at 25°C is preferably 1.62 or more, more preferably 1.65 or more, and even more preferably 1.66 or more. The reason is that when used in an optical lens, it can be thinned, or the refractive index difference with the transparent electrode can be reduced in an optical film to make the transparent electrode less obvious, or an anti-reflection function can be imparted by combining with a low refractive index layer, or the light extraction efficiency from the light-emitting element part can be improved in LED packaging materials. In addition, the upper limit of the refractive index is not particularly limited, and the higher the value, the better. In other words, from the viewpoint of balance with viscosity, it is preferably 1.62 or more and 1.70 or less, and more preferably 1.65 or more and 1.69 or less.
[0152] [Method for producing cured product]
[0153] The method for producing the cured product of the present embodiment is not particularly limited, and for example comprises: a coating step of coating the active energy ray-curable composition of the present embodiment described above on a substrate such as a transparent film; and a curing step of irradiating the film of the active energy ray-curable composition obtained by the coating step with active energy rays and curing it.
[0154] As a coating method for a substrate such as a transparent film, a known method can be used, for example, a method using a rod or a wire rod, or various coating methods such as micro-gravure, gravure, die, curtain, lip, slot or spin.
[0155] The active energy ray can be used without particular limitation as long as it is an active energy ray that causes the curable composition of the present invention to cure, but ultraviolet rays are particularly preferably used.
[0156] As the source of ultraviolet rays, there are fluorescent chemical lamps, black light lamps, low-pressure, high-pressure, and ultra-high-pressure mercury lamps, metal halide lamps, sunlight, etc. For example, an 80W high-pressure mercury lamp can be used.
[0157] The intensity of ultraviolet irradiation can be kept constant, or the physical properties after curing can be fine-tuned by changing the intensity during curing. For example, when using an 80W high-pressure mercury lamp in a nitrogen atmosphere, the intensity can be changed from 0.5 to 3.0 kJ / m 2 The energy value of ultraviolet radiation.
[0158] As active energy rays, for example, visible light and electron beam-type active energy rays may be used in addition to ultraviolet rays.
[0159] (Optical sheet)
[0160] The optical sheet of this embodiment can be formed using the cured product of this embodiment described above. The optical sheet of this embodiment can also include, for example, a substrate and the cured product of this embodiment described above formed on the substrate.
[0161] The optical sheet of this embodiment may also have, for example, a fine pattern layer such as a fine concavo-convex structure which is a cured product of the active energy ray-curable composition of the present embodiment and a transparent substrate. In addition, the fine pattern layer such as the fine concavo-convex structure may also have a fine concavo-convex structure of 10 to 500 μm on its surface, for example, depending on the purpose of the optical sheet.
[0162] The cured product of the active energy ray-curable composition in the optical sheet of the present embodiment may have a smooth surface without having a fine concavo-convex structure. The shape can be appropriately selected according to various uses.
[0163] As said optical sheet, a polarizing film, a retardation film, an antireflection film, a brightness improvement film (a prism sheet, a microlens sheet, etc.), a light diffusion film, a hard coat film etc. are mentioned, for example.
[0164] [Base material]
[0165] As the substrate of this embodiment, there can be mentioned polyethylene terephthalate (PET), triacetyl cellulose (TAC), cycloolefin polymer (COP), cycloolefin copolymer (COC), polycarbonate, vinyl chloride, polymethacrylimide, polyimide, polyester, acrylic substrate with polymethyl methacrylate (PMMA) as the main component, glass, silicon wafer, etc.
[0166] The film thickness of the substrate of the present embodiment is preferably 1 to 300 μm, more preferably 5 to 100 μm.
[0167] Specific examples of the substrate of the present embodiment include a 125 μm polyethylene terephthalate (PET) substrate (trade name: A4300, manufactured by Toyobo Industries, Ltd.) used in Examples.
[0168] When the substrate is transparent, a transparent substrate used in conventionally known optical sheets such as prism sheets can be used. For example, the transparent substrate described in Patent Document 2 can be used.
[0169] The transparent substrate may be a resin substrate or a glass substrate.
[0170] Preferred transparent resin substrates include acrylic resins, polycarbonate resins, vinyl chloride resins, polymethacrylimide resins, polyimide resins, polyester resins, cycloolefin polymer (COP) resins, cycloolefin copolymer (COC) resins, and triacetyl cellulose (TAC) resins.
[0171] The transparent substrate may be in a long strip shape or in a leaf shape having a predetermined size.
[0172] The thickness of the transparent substrate is usually preferably 50 to 500 μm, but is not limited thereto.
[0173] The light transmittance of the transparent substrate is preferably 100% for installation on the front surface of a display, and preferably 85% or more.
[0174] The above-mentioned transparent substrate may also be subjected to known extinction treatment (formation of light diffusive micro-concavoconvex), antistatic treatment or antireflection treatment etc. on its surface as required. In addition, extinction treatment, antistatic treatment or antireflection treatment etc. may also be implemented between the transparent resin and the substrate, and these may be freely combined and used.
[0175] [Method for producing optical sheet]
[0176] The method for manufacturing the optical sheet of the present embodiment is not particularly limited, and for example includes: a step of applying the active energy ray-curable composition of the present embodiment to the substrate; and a step of irradiating active energy rays such as ultraviolet rays to form a cured coating. The method for manufacturing the laminate of the present embodiment preferably includes, for example, the following steps: a step of applying the active energy ray-curable composition of the present embodiment to a triacetylcellulose substrate film (TAC substrate film) having a thickness of 40 to 100 μm; and irradiating ultraviolet rays of 0.5 to 3.0 kJ / m with a 60 to 100 W high pressure mercury lamp in a nitrogen atmosphere. 2 , a step of forming a cured coating film having a thickness of 5 to 20 μm on the TAC substrate film.
[0177] As a method for manufacturing the optical sheet of the present embodiment, for example, as shown in FIG. 2 of the patent document (Japanese Patent Publication No. 2009-37204), the above composition is added to a mold having a desired fine pattern shape such as a fine concave-convex structure, a transparent substrate layer is superimposed thereon, the transparent substrate layer is pressed onto the composition using a laminator, etc., and the composition is cured by ultraviolet light, etc., thereby forming a fine pattern shape such as a fine concave-convex structure. Then, by peeling off or removing the mold having a fine pattern shape, an optical sheet having an optical function embodiment portion having a desired fine pattern shape on the transparent substrate layer is obtained.
[0178] <Prism Sheet>
[0179] As a specific example of the optical sheet of the present embodiment, a prism sheet can be cited. The prism sheet has, for example, a fine concave-convex structure layer which is a cured product of the active energy ray-curable composition of the present embodiment and a transparent substrate. In addition, the fine concave-convex structure layer has a fine concave-convex structure with a period P of 10 to 100 μm on its surface. The thickness of the fine concave-convex structure layer is, for example, 5 μm to 100 μm.
[0180] Generally, when the content of monofunctional (meth)acrylate (B1) in the composition is high, the polymer structure after curing has fewer branches, so there is a tendency for the mold release of the cured product to deteriorate. The present invention focuses on this tendency and improves the mold release by setting the mass blending [(A) / (B1)] of the inorganic nanoparticles (A) relative to the above-mentioned monofunctional (meth)acrylate (B1) to the range of 0.5 to 3. In more detail, it is believed that if [(A) / (B1)] is in the range of 0.5 to 3, it is easy for the inorganic nanoparticles (A) to be present on the surface when the composition is applied to the substrate (i.e., near the interface between the composition and the mold), which can reduce the adhesion of the cured product of the composition to the mold.
[0181] In addition, since the composition contains a silane coupling agent and a (meth)acryloyl-containing phosphate dispersant, the mold release property of the cured product can be further improved. It is believed that this is because the inorganic nanoparticles (A) are compatible with the components other than (A) in the composition through the silane coupling agent and the phosphate dispersant, thereby improving the strength of the cured product, and when the cured product and the mold are peeled off, the cured product becomes less likely to remain on the mold.
[0182] In addition, when the present invention uses o-phenylphenol (EO) acrylate, biphenyl methyl acrylate, acrylate (1-naphthyl) methyl ester as monofunctional (methyl) acrylate (B1), substrate adhesion is particularly improved. It is believed that these compounds are monomers with relatively high glass transition temperatures, and the film hardness of the composition is also improved. This hardness improvement and other multiple factors are complicatedly overlapped, thereby having the possibility of improving substrate adhesion.
[0183] When phenoxyethyl acrylate was used as the monofunctional (meth)acrylate (B1), the substrate adhesion was also good. This is probably because phenoxyethyl acrylate contains a highly polar ethylene oxide structure in the molecule, which increases the interaction with the substrate.
[0184] As described above, the configurations that can further obtain the effects and the mechanisms that are presumed to exhibit these effects have been described, but the present invention is not limited to these configurations, and the problems of the present invention can be solved in a composition that does not contain a silane coupling agent and a phosphate-based dispersant, or a composition that does not contain a specific compound that is a monofunctional (meth)acrylate (B1).
[0185] Example
[0186] The present invention will be described in detail below based on examples, but the present invention is not limited thereto.
[0187] (raw material)
[0188] “Zirconium oxide (A)”: UEP-100 (manufactured by Daiichi Kizen Chemical Industry Co., Ltd.)
[0189] “Dispersant (D)” (phosphate ester compound): Dispersant D-1 (a compound represented by the following structural formula (1))
[0190]
[0191] (Where R 1 is methyl, R 2 is an ethylene chain having 2 carbon atoms, x is 5, y is 2 (average value), and n is an integer from 1 to 3)
[0192] “Silane coupling agent (E)”: KBM-503 (manufactured by Shin-Etsu Chemical Co., Ltd., 3-(trimethoxysilyl)propyl methacrylate)
[0193] "Monofunctional (meth)acrylate compound (B1)":
[0194] o-Phenylphenol (EO) acrylate, trade name: KOMERATE A011 (manufactured by Green Chemical Co., Ltd.)
[0195] Biphenyl methyl acrylate, trade name: MIRAMER M1192 (manufactured by MIWON SPECIALTY CHEMICAL CO., LTD.)
[0196] 3-Phenoxybenzyl acrylate, trade name: KOMERATE A008 (manufactured by Green Chemical Co., Ltd.)
[0197] (1-Naphthyl)methyl acrylate, trade name: LIGHT ACRYLATE NMT-A (manufactured by Kyoei Chemical Co., Ltd.)
[0198] Phenoxyethyl acrylate, trade name: Photomer 4035 (manufactured by IGM Resins Inc.)
[0199] Benzyl acrylate, trade name: MIRAMER M1182 (manufactured by MIWON SPECIALTY CHEMICAL CO., LTD.)
[0200] "Multifunctional (meth)acrylate compound (B2)"
[0201] A mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (containing about 60% of pentaerythritol triacrylate), trade name: ARONIX M305 (manufactured by Toagosei Co., Ltd.)
[0202] “Photopolymerization initiator (C)”:
[0203] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide, trade name: Runtecure 1108 (manufactured by Runtec Chemical Co., Ltd.)
[0204] <Liquid Refractive Index>
[0205] The active energy ray-curable composition was directly applied to the prism of the Abbe refractometer and measured at 25° C. Measurement wavelength: 589 nm.
[0206] <Film refractive index>
[0207] The active energy ray-curable composition is sandwiched between a glass plate and a transparent PET film (trade name: A4300, thickness: 125 μm, manufactured by Toyobo) as a transparent substrate and is stretched to a film thickness of about 10 μm by a rubber hand-held roller. Afterwards, the active energy ray is irradiated to cure it. Next, the PET film is peeled off from the glass plate together with the active energy ray-cured resin layer, and a cured coating of the curable composition is formed on the surface of the above-mentioned substrate. The refractive index of the coating is measured using PRISMCOUPLER MODEL 2010 / M (manufactured by Metricon).
[0208] "Irradiation conditions"
[0209] Light source: Ultraviolet light from ultra-high pressure mercury lamp
[0210] Total light intensity: 400mJ / cm 2
[0211] "Measurement conditions"
[0212] Wavelength: 594nm
[0213] Measurement mode: single film
[0214] <Viscosity>
[0215] Evaluation of viscosity The viscosity at a temperature of 25° C. was measured using an E-type rotational viscometer (“TVE-25H” manufactured by Toki Sangyo Co., Ltd.).
[0216] <Mold release>
[0217] After the active energy ray-curable composition was filled between a nickel-phosphorus mold and a PET film (trade name: A4300, thickness: 125 μm, manufactured by Toyobo Industries), it was irradiated from the PET film side with an ultra-high pressure mercury lamp at 400 mJ / cm 2 The nickel-phosphorus mold is formed with a linearly arranged concave-convex shape of unit prisms (pitch 50 μm, height 25 μm). The PET film is transparent and has been subjected to an easy-to-adhere treatment as a transparent substrate. Next, the PET film is peeled off from the mold together with the resin layer composed of the active energy ray-curable composition to produce a cured product with a PET film shape to which the desired shape has been transferred. The area of the resin layer remaining on the mold during the peeling is visually evaluated and judged as follows.
[0218] ◎: No resin layer remaining on the mold
[0219] ○: Part of the resin layer remains on the mold
[0220] ×: The entire surface remains on the mold
[0221] <Adhesion to substrate>
[0222] Adhesion was evaluated by a cross-cut test method using a cured product with a PET film shape obtained by the same method as the above-mentioned <Mold Releasability> evaluation method.
[0223] The test surface was cut with a cutter and a cutting guide, with 11 cuts reaching the bottom layer at 1 mm intervals to form 100 checkerboards. Then, Cellotape (registered trademark) was strongly pressed onto the checkerboard portion, and the end of the tape was torn off all at once, and the number of grids where the resin layer was not peeled off was counted for judgment.
[0224] (Example 1)
[0225] 45.00 parts by mass of UEP-100 as zirconium oxide, 6.75 parts by mass of phosphate ester 1 (dispersant D-1) as phosphate ester, 4.50 parts by mass of KBM-503 as silane coupling agent (1) and 96.8 parts by mass of methyl ethyl ketone (hereinafter referred to as "MEK") were mixed and stirred for 30 minutes with a dispersing mixer to perform coarse dispersion. Then, the obtained mixed solution was dispersed using a medium-type wet disperser ("Star Mill LMZ-015" manufactured by Ashizawa Finetech Co., Ltd.) and zirconium oxide beads with a particle size of 100 μm. While confirming the particle size in the middle, the dispersion treatment was performed for a residence time of 100 minutes to obtain an inorganic fine particle dispersion.
[0226] In the inorganic fine particle dispersion, 37.25 parts by mass of a compound (B1-2) as a monofunctional (meth) acrylate (B1): MIRAMER M1192 (manufactured by MIWON SPECIALTY CHEMICAL CO., LTD.) and 5.00 parts by mass of a compound (B2-1) as a multifunctional (meth) acrylate compound (B2): ARONIX M305 (manufactured by Toa Synthetics Co., Ltd.) were added, and the volatile components were removed by decompression while heating with an evaporator. Furthermore, 0.7 parts by mass of Runtecure 1108 (manufactured by Runtec Chemical Co., Ltd.) as a photopolymerization initiator was added to prepare the active energy ray curable composition P1 (composition P1) of the present embodiment. The liquid refractive index and viscosity of the composition P1 were evaluated using the above-mentioned evaluation method. In addition, the film refractive index, mold release property, and substrate adhesion of the cured product of the composition P1 were evaluated. These results are shown in Table 1.
[0227] (Examples 2 to 14, Comparative Examples 1 to 6)
[0228] In each example, except for using the components and composition ratios shown in Table 1, the same method as in Example 1 was used to prepare compositions P2 to P14 and cP1 to cP6 of Examples 2 to 14 and Comparative Examples 1 to 6, respectively. It should be noted that the amount of MEK used was 2.15 times the amount of the inorganic nanoparticles mixed as in Example 1. The liquid refractive index, film refractive index, and viscosity of each composition were evaluated in the same manner as in Example 1. In addition, the mold release and substrate adhesion of the cured product of each composition were evaluated. These results are shown in Table 1.
[0229] [Table 1]
[0230]
[0231] In the table, the meanings of each record are as follows.
[0232] The compositions of Comparative Examples 1 to 6 had poor releasability and could not be produced into prism sheets, so the adhesion test could not be performed (measurement was not possible).
[0233] [(A) / (B1)]: mass ratio of the inorganic nanoparticles (A) to the monofunctional (meth)acrylate (B1)
[0234] [(B1) / (B)]: Content of the monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B) (unit: mass %)
[0235] [Compound containing a compound containing two aromatic rings in one molecule / (B)]: Content of the compound containing a compound containing two aromatic rings in one molecule in the (meth)acrylate compound (B) (unit: mass %)
[0236] Inorganic nanoparticles (A) (1): zirconium oxide, trade name: UEP-100 (manufactured by Daiichi Kizenso Kagaku Kogyo Co., Ltd.)
[0237] Phosphate ester compound (1): dispersant D-1, a compound represented by the above structural formula (1)
[0238] Silane coupling agent (E) (1): 3-(trimethoxysilyl)propyl methacrylate, trade name: KBM-503 (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0239] Compound (B1-1): o-phenylphenol (EO) acrylate, trade name: KOMERATE A011 (manufactured by Green Chemical Co., Ltd.)
[0240] Compound (B1-2): biphenyl methyl acrylate, trade name: MIRAMER M1192 (manufactured by MIWON SPECIALTYCHEMICAL CO., LTD.)
[0241] Compound (B1-3): 3-phenoxybenzyl acrylate, trade name: KOMERATE A008 (manufactured by Green Chemical Co., Ltd.)
[0242] Compound (B1-4): (1-naphthyl)methyl acrylate, trade name: LIGHT ACRYLATE NMT-A (manufactured by Kyoei Chemical Co., Ltd.)
[0243] Compound (B1-5): phenoxyethyl acrylate, trade name: Photomer 4035 (manufactured by IGM Resins Inc.)
[0244] Compound (B1-6): benzyl acrylate, trade name: MIRAMER M1182 (manufactured by MIWON SPECIALTY CHEMICAL CO., LTD.)
[0245] Compound (B2-1): a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (containing about 60% of pentaerythritol triacrylate), trade name: ARONIX M305 (manufactured by Toagosei Co., Ltd.)
[0246] Photopolymerization initiator (C): 2,4,6-trimethylbenzoyldiphenylphosphine oxide, trade name: Runtecure 1108 (manufactured by Runtec Chemical Co., Ltd.)
[0247] (Inspection)
[0248] As shown in Table 1, in Examples 1 to 14 in which the content of the monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B) is 70% by mass or more and the mass mixing ratio of the inorganic nanoparticles (A) to the monofunctional (meth)acrylate (B1) [(A) / (B1)] is in the range of 0.5 to 3, it can be confirmed that the composition has a high refractive index and a low viscosity, and the mold release property of the cured product is good and the film refractive index is high.
[0249] Among them, in Examples 1 to 9 and 12 to 14 in which at least any one of the compounds (B1-1) (o-phenylphenol (EO) acrylate), (B1-2) (biphenyl methyl acrylate), (B1-4) ((1-naphthyl) methyl acrylate), (B1-5) (phenoxyethyl acrylate) and (B2-1) (pentaerythritol triacrylate (containing pentaerythritol tetraacrylate)) is used as the (meth)acrylate compound (B), it can be confirmed that the substrate adhesion is better.
[0250] Furthermore, in Examples 11 to 13 using a compound containing two aromatic rings in one molecule as the monofunctional (meth)acrylate (B1), the refractive index is further improved compared to Examples 9 and 10 using a compound not containing two aromatic rings in one molecule as the monofunctional (meth)acrylate (B1). On the other hand, in Comparative Examples 1 to 5 in which the mass mixing ratio [(A) / (B1)] of the inorganic nanoparticles (A) to the monofunctional (meth)acrylate (B1) is less than 0.5, the mold release property of the cured product is poor, and thus a prism sheet cannot be made.
[0251] In addition, the refractive index of Comparative Example 6 which did not contain the inorganic nanoparticles (A) was significantly poor, and good releasability was not obtained.
Claims
1. An active energy ray-curable composition comprising inorganic nanoparticles (A), a (meth)acrylate compound (B) and a photopolymerization initiator (C), The (meth)acrylate compound (B) comprises a monofunctional (meth)acrylate (B1), The content of the monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B) is 70% by mass or more, The mass ratio of the inorganic nanoparticles (A) to the monofunctional (meth)acrylate (B1) [(A) / (B1)] is in the range of 0.5 to 3.
2. The active energy ray-curable composition according to claim 1, wherein The content of the inorganic nanoparticles (A) in the active energy ray-curable composition is 30% by mass or more.
3. The active energy ray-curable composition according to claim 1 or 2, wherein The inorganic nanoparticles (A) are at least one selected from the group consisting of zirconium oxide, silicon dioxide, barium sulfate, zinc oxide, barium titanate, cerium oxide, aluminum oxide, and titanium oxide.
4. The active energy ray-curable composition according to claim 1 or 2, wherein The (meth)acrylate compound (B) further comprises a multifunctional (meth)acrylate (B2), The content of the monofunctional (meth)acrylate (B1) in the (meth)acrylate compound (B) is in the range of 70 to 90% by mass, The content of the polyfunctional (meth)acrylate (B2) in the (meth)acrylate compound (B) is in the range of 10 to 30% by mass.
5. The active energy ray-curable composition according to claim 1 or 2, wherein The monofunctional (meth)acrylate (B1) includes a compound having two aromatic rings in one molecule.
6. The active energy ray-curable composition according to claim 5, wherein The content of the compound containing two aromatic rings in one molecule in the monofunctional (meth)acrylate (B1) is 50% by mass or more.
7. The active energy ray-curable composition according to claim 1 or 2, further comprising a dispersant (D), The dispersant (D) comprises a phosphate compound, The phosphate ester compound has at least one (meth)acryloyl group and at least one polyester chain. 8 . The active energy ray-curable composition according to claim 1 , which has a viscosity at 25° C. of 1,200 mPa·s or less. 9 . A cured product of the active energy ray-curable composition according to claim 1 . 10 . The cured product according to claim 9 , which has a refractive index (589 nm) at 25° C. of 1.65 or more.
11. An optical sheet comprising the cured product according to claim 9. 12 . An optical sheet comprising the cured product according to claim 10 .
